Prarancangan Pabrik Propilen Glikol Dari Gliserol Dengan Disain Alat Utama Reaktor Hidrogenasi - Artha, Ulfa Dwi; Fadli, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Propylene glycol or 1,2-propadienol is an organic compound which has low toxicity and good formulation properties. Propylene glycol can be used as a preservative or solvent in the food industry, softener or moisturizer in the cosmetic industry, drug formulas in the pharmaceutical industry, additives that function as viscosity and color stabilizers in the paint industry, and others. Application of propylene glycol is vast, so that the demand for propylene glycol increases from year to year. However, until now, all propylene glycol needs in Indonesia still rely on imports. Therefore, it is necessary to establish a propylene glycol factory in Indonesia. The pre-design of this plant is carried out in several steps, namely collecting data sources to support the establishment of the plant, calculating mass and energy balances, calculating heat and mass exchange networks, calculating and designing hydrogenation reactors and their supporting accessories, and economic analysis. In the pre-design of this plant, a reactor was designed in the form of a hydrogenation reactor which functions as a reaction site for acetol with hydrogen gas. The type of reactor used is a fixed bed multitube reactor with a temperature of 300 Â° C and a pressure of 14 bar. The hydrogenation reactor has 48 tubes, 5,0627 m high, 0,4382 m outside diameter, and uses skirt support.Keywords: Propylene glycol, glycerol, hydrogenation reactor, economic analysis